13C dynamic nuclear polarization using isotopically enriched 4‐oxo‐TEMPO free radicals. (17th July 2016) - Niedbalski, Peter; Parish, Christopher; Kiswandhi, Andhika; Lumata, Lloyd
Abstract : The nitroxide‐based free radical 2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy (TEMPO) is a widely used polarizing agent in NMR signal amplification via dissolution dynamic nuclear polarization (DNP). In this study, we have thoroughly investigated the effects of 15 N and/or 2 H isotopic labeling of 4‐oxo‐TEMPO free radical on 13 C DNP of 3 M [1‐ 13 C] sodium acetate samples in 1 : 1 v/v glycerol : water at 3.35 T and 1.2 K. Four variants of this free radical were used for 13 C DNP: 4‐oxo‐TEMPO, 4‐oxo‐TEMPO‐ 15 N, 4‐oxo‐TEMPO‐d16 and 4‐oxo‐TEMPO‐ 15 N, d16 . Our results indicate that, despite the striking differences seen in the electron spin resonance (ESR) spectral features, the 13 C DNP efficiency of these 15 N and/or 2 H‐enriched 4‐oxo‐TEMPO free radicals are relatively the same compared with 13 C DNP performance of the regular 4‐oxo‐TEMPO. Furthermore, when fully deuterated glassing solvents were used, the 13 C DNP signals of these samples all doubled in the same manner, and the 13 C polarization buildup was faster by a factor of 2 for all samples. The data here suggest that the hyperfine coupling contributions of these isotopically enriched 4‐oxo‐TEMPO free radicals have negligible effects on the 13 C DNP efficiency at 3.35 T and 1.2 K. These results are discussed in light of the spin temperature model of DNP. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : 15 N and/or 2 H‐enriched 4‐oxo‐TEMPO free radicals have the same efficiency in 13 C dynamic nuclear polarization at 3.35 T and 1.2 K despite their differences in hyperfine coupling. The 13 C polarization levels all doubled in the same manner and the polarization buildup times were cut into half when deuterated glassing solvents were used for these free radicals.